The impact of reforestation in the northeast United States on precipitation and surface temperature - Clark, Allyson, author; Randall, David, advisor; Denning, A. Scott, committee member; Binkley, Dan, committee member (Colorado State University. Libraries, 2013)
Since the 1920s, forest coverage in the northeastern United States has recovered from disease, clearing for agricultural and urban development, and the demands of the timber industry. Such a dramatic change in ground cover can influence heat and moisture fluxes to the atmosphere, as measured in altered landscapes in Australia, Israel, and the Amazon. In this study, the impacts of recent reforestation in the northeastern United States on summertime precipitation and surface temperature were quantified by comparing average modern values to 1950s values. Weak positive (negative) relationships between reforestation and average monthly precipitation and daily minimum temperatures (average daily maximum surface temperature) were found. There was no relationship between reforestation and average surface temperature. Results of the observational analysis were compared with results obtained from reforestation scenarios simulated with the BUGS5 global climate model. The single difference between the model runs was the amount of forest coverage in the northeast United States; three levels of forest were defined - a grassland state, with 0% forest coverage, a completely forested state, with approximately 100% forest coverage, and a control state, with forest coverage closely resembling modern forest coverage. The three simulations were compared, and had larger magnitude average changes in precipitation and in all temperature variables. The difference in magnitudes between the model simulations observations was much larger than the difference in the amount of reforestation in each case. Additionally, unlike in observations, a negative relationship was found between average daily minimum temperature and amount of forest coverage, implying that additional factors influence temperature and precipitation in the real world that are not accounted for in the model.
Keywords: climatology; reforestation